Relationship between Selected Motor Fitness and Psychological Variables with Playing Ability of Male Volleyball Players: - (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of the study is to find out the relationship of motor fitness and psychological variables with playing ability of inter college Volleyball male players. Thirty outside hitter inter-college level Volleyball players from different colleges of Panjab University who have represented at Inter - college Volleyball tournament were purposively selected as subjects for this study and their age were ranged between from 18 to 23 years. With respect to motor fitness variables four variables such as speed, agility, strength endurance, flexibility and three psychological variables such as Cognitive anxiety, Somatic anxiety and Self- Confidence were taken into consideration under the independent variables. The playing ability measured as dependent variable and it was judged by Coaches Rated Scale on 10 point scale. Speed was assessed by 30 Meter Dash, agility was assessed by 4 x 10 Meter Shuttle Run, Strength endurance was assessed by Bent Knee Sit Ups and Flexibility was measured by Sit Reach Tests. Cognitive anxiety, Somatic anxiety and Self- Confidence were measure by Competitive state anxiety inventory (CSAI 1990). The collected data was used to find out the relationship among the selected dependent and independent variables. The Karl Pearson’s Product Moment Coefficient of Correlation was used to find out the relationship between the selected variables. The level of significance was fixed at 0.05. The results concluded that the playing ability of volleyball male players had positively correlation with agility, cognitive anxiety and self –confidence and rest of the selected variables had not shown any significant relationship with playing ability. The motor fitness and psychological variable are most crucial for enhancement of playing ability of Volleyball players.